2014
DOI: 10.1371/journal.pone.0091324
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus iniae SF1: Complete Genome Sequence, Proteomic Profile, and Immunoprotective Antigens

Abstract: Streptococcus iniae is a Gram-positive bacterium that is reckoned one of the most severe aquaculture pathogens. It has a broad host range among farmed marine and freshwater fish and can also cause zoonotic infection in humans. Here we report for the first time the complete genome sequence as well as the host factor-induced proteomic profile of a pathogenic S. iniae strain, SF1, a serotype I isolate from diseased fish. SF1 possesses a single chromosome of 2,149,844 base pairs, which contains 2,125 predicted pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 108 publications
(101 reference statements)
1
22
0
Order By: Relevance
“…This finding was in agreement with data from a previous study on the CRISPR/Cas systems of S.iniae SF1 [19].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This finding was in agreement with data from a previous study on the CRISPR/Cas systems of S.iniae SF1 [19].…”
Section: Resultssupporting
confidence: 93%
“…By 2015, eight available genomes of S. iniae were recorded on the NCBI database: YSFST01-82, SF1, 9117, CAIM 527, ISET0901, IUSA1, KCTC 11634BP and ISNO (Table 1). While the complete genome sequence of S. iniae SF1 has been reported [19], comparative genomic analysis of closely related S. iniae species is yet to be conducted. In this study, we have reported the complete genome sequence of S. iniae DX09, a strain isolated from cultured catfish (Ictalurus punctatus) (Supplementary Figure 1) in the Guangxi region of China, for the first time and compared it to all known S. iniae genomes available in the NCBI database.…”
Section: Introductionmentioning
confidence: 99%
“…The putative C3-degrading protease was published in the complete genome sequence of S. iniae SF1 isolated from fish by Zhang et al (GenBank ID AGM99589.1) (Zhang et al, 2014). However in the two later complete sequences of S.iniae from Tilapia i.e.…”
Section: The Putative C3-degrading Proteasementioning
confidence: 99%
“…(AHY18370.1 and AHY16506.1) (Pridgeon et al, 2014a, b) although it has 99-100% identity to C3-degrading protease of Zhang et al, (2014) by BLAST, which warrants further investigation. The protease coding gene cppA was also found in other Streptococci such as S. dysgalactiae subsp.…”
Section: The Putative C3-degrading Proteasementioning
confidence: 99%
See 1 more Smart Citation